Morphoanatomy and Phytochemical Content of Sente Leaves (Alocasia macrorrhizos (L.)G.Don) under Different Light Intensity in Arboretum Universitas Padjadjaran - Rachma, Nadhira Zaachrany; Mutaqin, Asep Zainal; Setiawati, Tia; Nurzaman, Mohamad; Hasan, Rusdi (UNIVERSITAS PGRI MADIUN, 2024)
Light intensity in plants influences their growth potential as well as their morphological, anatomical, and physiological structures. This study aimed to observe the leaf area, leaf thickness, leaf type, stomatal type, stomatal density, chlorophyll content, and phytochemical content of Sente leaves (Alocasia macrorrhizos) in two locations with different light intensities. This exploratory research used a survey method to determine the research location, and environmental parameter measurements was used as supporting data. Morphological and anatomical parameters and chlorophyll content were assessed using a quantitative approach, while phytochemical content was determined qualitatively and analyzed descriptively. The results showed differences in the morphology, anatomy, chlorophyll content, and phytochemicals of Sente leaves in varying light intensities. Morphologically, the leaves of Sente plants in shaded locations had larger surface areas, were thinner, and appeared greener compared to those in unshaded locations. The stomatal density of leaves in unshaded areas was higher (76.43 cells/mm ²) compared to shaded areas (56.05 cells/mm ²). The chlorophyll content in shaded locations was higher (82.03 CCl) than in unshaded locations (41.7 CCl). Phytochemical tests for flavonoids and saponins showed higher compound levels in leaves from unshaded locations, while tannin tests revealed higher levels in shaded locations compared to unshaded ones. Meanwhile, tests for alkaloids and quinones yielded negative results.